Research stand for microplasma surface treatment of materials at atmospheric pressure - S. V. Bordusau; S. I. Madveika; A. L. Barakhoyeu; O. I. Tsikhan; A. A. Maiseyeu (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
A research stand for microplasma treatment of object surfaces with the ability to move the discharge zone along the object using a program-controlled linear stepper motor has been developed. The design of the stand allows the use of different types of plasma generation systems, as well as processing with feeding of various gases such as air, nitrogen, oxygen, etc. into the discharge zone. The research bench is equipped with measuring equipment for monitoring the electrical and physical characteristics of the discharge (digital oscilloscopes, optical emission spectrometer, air ion meter, etc.). A microhardness tester, goniometer, interference microscope, tribometer, tensile testing machine, etc. can be used to further evaluate the quality and characteristics of the treated surfaces. Examples of the electrical characteristics of discharge devices tested as part of the research stand, optical emission spectroscopy of plasma, and results of measurements of the contact angle of treated objects surfaces are given.